A self-repairing heat storage composite material and preparation method thereof
The self-healing heat storage composite material prepared by the emulsion template method and cross-linking reaction solves the problem of leakage of the heat storage composite material under external force, and realizes the self-healing of the material and the maintenance of efficient heat storage performance.
Patent Information
- Application Number
- CN202310445315.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-24
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2043-04-24
AI Technical Summary
Thermal storage composite is prone to local rupture or fracture under the action of external forces, resulting in leakage of liquid phase change materials, limiting its use in practical applications.
An oil-in-water emulsion containing phase change materials was prepared by the emulsion template method, and a heat storage composite material with self-healing properties was formed by reacting a crosslinking agent with a water-soluble polymer. After contacting the fracture surface, the material can be broken and regenerated by chemical bonds, thereby realizing the reconstruction of the three-dimensional network structure, thereby repairing the damaged area by itself.
The self-repair function of heat storage composite materials is realized, which can quickly repair damaged areas in a short period of time, and the mechanical properties and thermal properties of the repaired materials have no significant changes, and the heat storage density and thermal enthalpy value are also maintained at a high level.
Smart Images

Figure CN116535791B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of heat storage composite material preparation, and in particular relates to a self-repairing heat storage composite material and a preparation method thereof. Background Art
[0002] The rapid development of society requires people to produce, store and utilize energy more efficiently. Thermal energy is the energy of life. Reasonable matching of thermal energy supply and demand can greatly improve the efficiency of new energy (such as solar energy) and thermal energy recovery. Phase change materials can absorb a large amount of heat when they melt from solid to liquid, and release a large amount of heat when they transform from liquid to solid, while keeping the temperature basically unchanged; this process is reversible, so it can be repeatedly used to store and release heat. In order to meet practical needs, it is often necessary to encapsulate or shape the phase change material. Microcapsule coating phase change material is a common method for preparing heat storage composite materials. The prepared phase change microcapsules have the advantage of large specific surface area, but low heat storage density. In recent years, phase change materials are used as emulsion dispersed phases, and polymerization and cross-linking are carried out in the emulsion continuous phase to solidify the emulsion to prepare heat storage composite materials, such as the literature "Encapsulating an organic phase change material within emulsion-templated poly (urethane urea) s. Polymer Chemistry 10 (12): 1498-1507". This heat storage composite material has the characteristics of large specific surface area and high heat storage density. However, the brittleness and other problems of this heat storage composite material limit its development. In order to solve these problems, heat storage composite materials prepared by template method with octadecane as dispersed phase have been reported. For example, the literature "Octodecane-cellulose nanofiber flexible composites for latent heat storage. Chemical Engineering Journal 425,131432" reported that octadecane was used as dispersed phase and cellulose nanofiber suspension was used as continuous phase. Through interfacial reaction, a high thermal enthalpy value (up to 250 J·g -1), low leakage and flexible heat storage composite materials, which solve the brittleness and leakage problems of phase change composite materials. In addition, the document "Emulsion-based, flexible and recyclable aerogel composites for latent heat storage. Journal of Colloid and Interface Science 627, 72-80" also reported the preparation of a renewable flexible heat storage composite material. The document used physically gel-cured cellulose nanocrystals stabilized, octadecane-encapsulated Pickering emulsion instead of traditional chemical cross-linking technology to prepare a flexible and recyclable heat storage composite material. The obtained composite material not only exhibits a controllable external shape, but the introduction of polyvinyl alcohol significantly reduces the leakage of encapsulated octadecane. The composite material exhibits good flexibility at temperatures above 30°C, does not break under a compression strain of 70%, and has a high heat capacity (up to 253 J·g -1 ) and reusable. In addition, the composite material is recyclable. It only needs to be dissolved in hot water to form an emulsion, and then freeze-dried to form a composite material again, which greatly increases the application range of the thermal storage composite material. Although flexible thermal storage composite materials can reduce the possibility of composite material breakage to a certain extent, thereby reducing leakage, in actual use, the composite material will undergo local rupture or fracture under the action of external forces; when the temperature is highly coated with the melting point of the phase change material, the liquid phase change material may still leak.
[0003] Therefore, in order to better meet practical needs (especially applications in the field of personal thermal management), heat storage composite materials with self-healing functions have become increasingly important. Summary of the invention
[0004] In order to solve the problem of liquid phase change material leakage caused by local fracture or rupture of heat storage composite materials, the purpose of the present invention is to provide a self-repairing heat storage composite material and its preparation method and application. The present invention adopts an emulsion template method to prepare an oil-in-water emulsion containing a phase change material, and prepares a heat storage composite material by cross-linking. The heat storage composite material has good self-repairing properties and can repair the damaged area by contacting the fracture surface in a short time. The porous structure formed by the emulsion template method is adjustable and has a large specific surface area, so that the material has a good heat storage density.
[0005] In order to solve the above-mentioned technical problems, this application provides the following technical solutions:
[0006] The present invention provides a method for preparing a self-repairing heat storage composite material, comprising the following steps:
[0007] (1) adding an oil phase to an aqueous phase and mixing them to obtain an oil-in-water emulsion; the oil phase is a phase change material, and the aqueous phase is an aqueous solution of a water-soluble polymer; the volume ratio of the oil phase to the aqueous phase is 0.4-1:1;
[0008] (2) Adding a crosslinking agent to the oil-in-water emulsion to undergo a crosslinking reaction to obtain the self-repairing heat storage composite material.
[0009] Preferably, the water-soluble polymer is selected from one or more of polyvinyl alcohol, sodium alginate, acrylamide, polyphosphazene, chitosan, polyethylene glycol, poly-L-lysine, polyethylene oxide, sodium polyacrylate, polyacrylic acid and polymethacrylic acid.
[0010] Furthermore, the water-soluble polymer is preferably polyvinyl alcohol, which has excellent film-forming properties and high-viscosity polyvinyl alcohol can disperse the emulsion droplets evenly and reduce the possibility of droplet accumulation.
[0011] Preferably, the water-soluble polymer accounts for 5-70% of the total weight of the water phase. The water-soluble polymer can increase the viscosity of the emulsion and reduce the possibility of accumulation of dispersed droplets. The water-soluble polymer has excellent film-forming properties and can form a film between the water and oil phases to achieve coating of the emulsion droplets and avoid leakage of the phase change material.
[0012] Preferably, the phase change material is selected from one or more of tetradecane, pentadecane, hexadecane, heptadecane, octadecane, nonadecane, eicosane, heneicosane, docosane, tricosane, tetracosane, pentacosane, hexacosane, heptacosane, octacosane and paraffin.
[0013] Preferably, in step (1), the mixing speed is 800-2000 rpm. High-speed stirring and shearing can make the droplets disperse more evenly.
[0014] Preferably, in step (1), the mixing time is 2-5 min.
[0015] Preferably, the mass ratio of the cross-linking agent to the aqueous phase is 0.1-0.5:1.
[0016] Preferably, the cross-linking agent is one of sodium tetraborate, ferric chloride and calcium dichloride.
[0017] Furthermore, the cross-linking agent is preferably sodium tetraborate, which can quickly cross-link with polyvinyl alcohol to form a gel.
[0018] Preferably, in step (2), the cross-linking reaction time is 1-3 minutes.
[0019] Specifically, the method for preparing the self-repairing heat storage composite material comprises the following steps:
[0020] The water phase is composed of a water-soluble polymer and water, and the phase change material is used as the oil phase. The phase change material is dropped into the aqueous solution and stirred at a speed of about 800-2000 rpm with an overhead stirrer. After the phase change material is added, stirring is continued for 2-5 minutes to improve the uniformity of the emulsion. The oil phase is dispersed in the water phase to form an oil-in-water emulsion. Sodium tetraborate is added to the emulsion and stirring is continued at 200-800 rpm for 1-3 minutes. When all the gel is adhered to the stirring rod, it is taken out and the sample is obtained.
[0021] The principle of the present invention is: the water-soluble polymer in the continuous phase of the present invention can be reversibly cross-linked to form a three-dimensional network structure, which realizes the solidification of the emulsion structure and coats the phase change material to prepare a heat storage composite material with self-healing properties. The high viscosity of the water-soluble polymer can also prevent the accumulation of emulsion droplets and form a relatively complete closed-cell structure. The self-healing property originates from the reversible chemical cross-linking between the polymer and the cross-linking agent. When the composite material comes into contact, the reversible cross-linking system of the polymer can achieve the reconstruction of the three-dimensional network structure by breaking and regenerating chemical bonds, thereby giving the hydrogel composite material self-healing properties.
[0022] Compared with CN114437670A "A renewable heat storage composite material and its preparation method", the present invention does not use particle stabilizers and adopts chemical crosslinking instead of physical gel. While maintaining high thermal enthalpy value and quasi-closed cell structure, a more stable three-dimensional crosslinked structure is formed to cover the phase change material. The long molecular chains generated by crosslinking can make the material flexible within a wide temperature range and quickly combine to regenerate long molecular chains after damage, so that the composite material can achieve the purpose of self-repair and regeneration.
[0023] The present invention also provides a self-repairing heat storage composite material prepared by the above preparation method.
[0024] The technical solution of the present invention has the following advantages compared with the prior art:
[0025] (1) The self-repairing heat storage composite material of the present invention adopts the emulsion template method technology, and the high porosity and specific surface area make the material have a high heat storage density. The heat storage composite material obtained by the present invention has self-repairing performance, can quickly repair the damaged area within 0-2 minutes, and the mechanical properties of the repaired material do not decrease; the composite material has a good heat storage density, and the thermal enthalpy value is 180-260 J·g -1 The heat storage density of the repaired composite material did not decrease significantly, and the thermal enthalpy value was 170-250 J·g -1 .
[0026] (2) The self-repairing heat storage composite material described in the present invention can be quickly repaired after being damaged, and the mechanical properties and thermal properties of the repaired composite material do not change significantly.
[0027] (3) The raw materials of the self-repairing heat storage composite material described in the present invention are all degradable materials, and the materials have good mechanical properties such as tension, compression, torsion and knotting. The heat storage composite material prepared by the present invention has good mechanical properties, a tensile strain of 40-110%, a compression modulus of about 2kPa under 70% compression deformation, and no leakage of phase change materials, which is superior to the heat storage density and mechanical properties of existing heat storage composite materials.
[0028] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the following is a description of the preferred embodiments of the present invention in conjunction with detailed drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a self-repair test diagram of the heat storage composite material according to Example 1 of the present invention;
[0030] Figure 2 is a scanning electron microscope image of a cross section of the heat storage composite material of Examples 1 to 3 of the present invention;
[0031] Figure 3 is a differential scanning calorimetry analysis diagram of Examples 1 to 3, Comparative Example 1 and Test Example 1 of the present invention;
[0032] Figure 4 1 is a leakage test diagram of Example 1 of the present invention and Comparative Example 1;
[0033] Figure 5 100 thermal cycle test graphs and data tables of the heat storage composite material of Example 3 of the present invention;
[0034] Figure 6 is a compressed data diagram of the self-repairing heat storage composite material of Examples 1 to 3 of the present invention;
[0035] Figure 7 It is a tensile data diagram of the self-repairing heat storage composite material of Examples 1 to 3 and Test Example 1 of the present invention. DETAILED DESCRIPTION
[0036] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.
[0037] Example 1
[0038] This embodiment provides a method for preparing a self-repairing heat storage composite material, the steps are as follows:
[0039] Dissolve 1g of polyvinyl alcohol in 9g of water and stir at 1200rpm for 3min until completely dissolved to obtain an aqueous phase. While maintaining mechanical stirring, drop 5g of octadecane into the aqueous phase dropwise, mix evenly to obtain an oil-in-water emulsion, add 1g of sodium tetraborate, continue stirring at 300rpm for 2min, until the cross-linked gel is completely adhered to the stirring rod and taken out to obtain a self-healing thermal storage composite material. The density of the composite material is 0.6g / cm 3 , the pore size is 55μm.
[0040] Example 2
[0041] This embodiment provides a method for preparing a self-repairing heat storage composite material, the steps are as follows:
[0042] Dissolve 1g of polyvinyl alcohol in 9g of water and stir at 1200rpm for 3min until completely dissolved to obtain an aqueous phase. While maintaining mechanical stirring, drop 7g of octadecane into the aqueous phase dropwise, mix evenly to obtain an oil-in-water emulsion, add 1g of sodium tetraborate, continue stirring at 300rpm for 2min, until the cross-linked gel is completely adhered to the stirring rod and taken out to obtain a self-healing thermal storage composite material. The density of the composite material is 0.7g / cm 3 , the pore size is 37μm.
[0043] Example 3
[0044] This embodiment provides a method for preparing a self-repairing heat storage composite material, the steps are as follows:
[0045] Dissolve 1g of polyvinyl alcohol in 9g of water and stir at 1200rpm for 3min until completely dissolved to obtain an aqueous phase. While maintaining mechanical stirring, drop 9g of octadecane into the aqueous phase dropwise, mix evenly to obtain an oil-in-water emulsion, add 1g of sodium tetraborate, continue stirring at 300rpm for 2min, until the cross-linked gel is completely adhered to the stirring rod and taken out to obtain a self-healing thermal storage composite material. The density of the composite material is 0.8g / cm 3 , the pore size is 27μm.
[0046] Example 4
[0047] This embodiment provides a method for preparing a self-repairing heat storage composite material, the steps are as follows:
[0048] Dissolve 1g of sodium alginate in 9g of water and stir at 800rpm for 2h until completely dissolved to obtain an aqueous phase. While maintaining mechanical stirring, drop 5g of tetradecane into the aqueous phase dropwise, mix evenly to obtain an oil-in-water emulsion, add 1g of calcium dichloride, continue stirring at 200rpm for 1min, until the cross-linked gel is completely attached to the stirring rod and taken out to obtain a self-healing thermal storage composite material.
[0049] Example 5
[0050] This embodiment provides a method for preparing a self-repairing heat storage composite material, the steps are as follows:
[0051] Dissolve 1g of sodium polyacrylate in 9g of water and stir at 2000rpm for 2min until completely dissolved to obtain an aqueous phase. While maintaining mechanical stirring, drop 5g of paraffin wax into the aqueous phase dropwise, mix evenly to obtain an oil-in-water emulsion, add 1g of ferric chloride, continue stirring at 800rpm for 3min, until the cross-linked gel is completely attached to the stirring rod and taken out to obtain a self-healing thermal storage composite material.
[0052] Comparative Example 1
[0053] 1g of polyvinyl alcohol was dissolved in 9g of water and stirred at 1200rpm for 3min until completely dissolved to obtain an aqueous phase. Under the condition of mechanical stirring, 9g of octadecane was added dropwise into the aqueous phase and mixed evenly to obtain an oil-in-water emulsion. No sodium tetraborate was added. The emulsion was placed in a -20℃ refrigerator and frozen for 1h, then taken out and melted. The above steps were repeated 5 times to obtain Comparative Example 1. The density of the composite material was 0.9g / cm 3 .
[0054] Test Example 1
[0055] Self-healing test: Figure 1 This is a self-repairing test diagram of the self-repairing heat storage composite material in Example 1 of the present invention. It can be seen that the dyed self-repairing heat storage composite material and the undyed composite material are attached together at ambient temperature, and the healed composite material is stretched after standing for several minutes. The composite material shows self-repairing and stretchability, and no fracture or octadecane leakage is found at the incision.
[0056] Test Example 2
[0057] The structures of the composite materials obtained in Examples 1 to 5 of the present invention and Comparative Example 1 were characterized and their performances were tested, as follows:
[0058] (1) Electron microscopy characterization: Figure 2a, b, and c are cross-sectional scanning electron microscope images of the self-repairing heat storage composite materials of Examples 1 to 3 of the present invention. The results show that there is an obvious closed-pore structure inside the composite material, and the completely closed pores are conducive to the storage of octadecane and reduce leakage during the phase change process.
[0059] (2) Heat storage test: Figure 3 The differential scanning calorimetry (-30-50°C) analysis test results of the heat storage composite materials of Examples 1 to 5, Comparative Example 1 and Test Example 1 of the present invention show that the heat storage composite materials of Examples 1 to 5 and Comparative Example 1 have strong heat storage capacity. The thermal enthalpy values of the composite materials of Examples 1 to 5 are between 180 and 260 J·g -1 The thermal enthalpy value of comparative example 1 is 224 J·g -1 The difference between the two is not big. The high heat storage density of the composite material is attributed to the high specific surface area and high content of phase change material brought by the porous structure. The heat storage density of the heat storage composite material in test example 1 is 250.1 J·g -1 , indicating that the heat storage density of the composite material has no obvious change after self-repair.
[0060] (3) Leakage test: Figure 4 3 is a leakage test diagram of the heat storage composite material of Example 1 and Comparative Example 1 of the present invention. It can be seen that after heating at 40°C for 8 hours, the mass loss of Example 1 is 1.3%, and the mass loss of Comparative Example 1 is 4.2%. The leakage of Comparative Example 1 is significantly greater than that of Example 1. This is because the gel formed by cross-linking sodium tetraborate and polyvinyl alcohol contains a large number of long-chain molecules, the gel wall is relatively strong, and the strong film-forming ability of polyvinyl alcohol can also effectively prevent the leakage of octadecane, while Comparative Example 1 forms a three-dimensional structure through hydrogen bonding. Under high temperature conditions, the gel wall is unstable and easily destroyed, causing liquid octadecane to leak out.
[0061] (4) Repeatability test: Figure 5 These are 100 thermal cycle test graphs and data graphs of the self-repairing heat storage composite material of Example 3 of the present invention. It can be seen that the heat storage capacity of the self-repairing heat storage composite material does not decrease significantly after 100 heating and cooling scans, and the cyclic heat storage efficiency is 99.1%, which has high reusability.
[0062] (5) Compression test: Figure 6 This is a compression data diagram of the self-repairing heat storage composite material of Examples 1-3 of the present invention. It can be seen that under 70% compression deformation, no damage to the composite material and no leakage of octadecane were found, and the compression modulus of the composite material was between 1.1-2.5 kPa.
[0063] (6) Tensile test: Figure 7It is a tensile data graph of the self-repairing heat storage composite material of Examples 1-3 and Test Example 1 of the present invention. It can be seen that the composite material is stretchable, the tensile strain can be as high as 110%, and the tensile modulus is between 16.5-18.7 kPa. The tensile strain of the repaired composite material is close to that of Comparative Example 1, as high as 68%, and the tensile modulus is 17.1 kPa, indicating that the mechanical properties of the damaged sample have not decreased after self-repair, which is attributed to the rapid binding of the long-chain molecules of the hydrogel.
[0064] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.
Claims
1. A method for preparing a self-repairing heat storage composite material, characterized in that: The following steps are involved: (1) adding an oil phase to an aqueous phase and mixing them to obtain an oil-in-water emulsion; the oil phase is a phase change material, and the aqueous phase is an aqueous solution of a water-soluble polymer; the volume ratio of the oil phase to the aqueous phase is 0.4-1:1; (2) A cross-linking agent is added to the oil-in-water emulsion to undergo a cross-linking reaction to obtain the self-repairing heat storage composite material; the water-soluble polymer is selected from one of polyvinyl alcohol, sodium alginate and sodium polyacrylate, and the cross-linking agent is selected from one of sodium tetraborate, ferric chloride and calcium dichloride.
2. The preparation method according to claim 1, characterized in that: The water-soluble polymer accounts for 5-70% of the total weight of the aqueous phase.
3. The preparation method according to claim 1, characterized in that: The phase change material is selected from one or more of tetradecane, pentadecane, hexadecane, heptadecane, octadecane, nonadecane, eicosane, heneicosane, docosane, tricosane, tetracosane, pentacosane, hexacosane, heptacosane, octacosane and paraffin.
4. The preparation method according to claim 1, characterized in that: In the step (1), the mixing speed is 800-2000 rpm.
5. The preparation method according to claim 1, characterized in that: In the step (1), the mixing time is 2-5 minutes.
6. The preparation method according to claim 1, characterized in that: The mass ratio of the cross-linking agent to the aqueous phase is 0.1-0.5:
1.
7. The preparation method according to claim 1, characterized in that: In the step (2), the cross-linking reaction time is 1-3 min.
8. A self-repairing heat storage composite material prepared by the preparation method according to any one of claims 1 to 7.
Citation Information
Patent Citations
Renewable heat storage composite material and preparation method thereof
CN114437670A
Preparation method of capsule wall hydrogen bond self-repairing type microcapsule phase change material
CN111690376A
PVA / HA double-network hydrogel as well as preparation method and application thereof
CN112940294A